Influence of Adhesive Restorations on Diffusion of H2O2 Released from a Bleaching Agent and Its Toxic Effects on Pulp Cells - Soares, Diana Gabriela [UNESP]; Pastana, Julia Vieira [UNESP]; Oliveira Duque, Carla Caroline de [UNESP]; Dias Ribeiro, Ana Paula; Basso, Fernanda Goncalves; Hebling, Josimeri [UNESP]; Souza Costa, Carlos Alberto de [UNESP] (Quintessence Publishing Co Inc, 2014)
Purpose: To assess the influence of adhesive restorations on hydrogen peroxide (H2O2) diffusion through enamel and dentin and its cytotoxicity to pulp (MDPC-23) cells.Materials and Methods: Sound and resin-restored enamel/dentin disks were stored in water for 24h or 6 months and adapted to artificial pulp chambers. Bleaching gels with 20% or 35% H2O2 were applied to the enamel surface for 45 min, and a culture medium in direct contact with the dentin surface (extract) was applied for 1 h to the MDPC-23 cells. Cell metabolism (MU assay) and cell morphology (SEM) were assessed. The amount of H2O2 in the extracts was also quantified (peroxidase/leuco-crystal violet reaction).Results: A significant reduction in cell metabolism was observed between the group bleached with the 35% gel and the control group (sound, nonbleached) (p < 0.05). The H2O2 diffusion was directly related to its concentration in the bleaching gel. The variables presence of restoration and time of water storage did not significantly influence H2O2 diffusion or cell metabolism for either of the bleaching gels (p > 0.05). All bleached groups presented alterations in cell morphology related to the concentration of H2O2 in the bleaching gel.Conclusion: The reduction in cell metabolism and the changes in cell morphology were H2O2-concentration dependent, having no relationship with the presence of either new or aged adhesive restorations on teeth subjected to bleaching therapies.
Keywords: odontoblasts; tooth bleaching; cytotoxicity